Willingness-to-pay for natural, organic, and conventional foods: The effects of information and meaningful labels. (April 2017) - McFadden, Jonathan R.; Huffman, Wallace E.
Abstract: Vague food labels and distorted product claims have persisted in the "natural" food industry, while organic claims can be certified by the U.S. Department of Agriculture (USDA). Using experimental methods and a sample of randomly selected subjects, we test food label and information treatment effects on subjects' willingness-to-pay (WTP) for organic, "natural, " and conventional foods. Random n th-price auctions are used to elicit WTP after subjects received one of five randomly assigned information treatments. We find large information effects, including asymmetric cross-market effects for natural and organic foods. Perhaps surprising is that organic premiums increase in response to subjects seeing the "natural" foods industry's perspective on its products. Demographics effects are also important. The results have practical implications for natural and organic food marketing and valuing products where there are vague claims about their attributes.